(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To evaluate the efficacy of enucleation in cats, highlighting the main indications, surgical approaches, postoperative recovery and sensory adaptation of felines after the procedure. Enucleation is a surgical intervention performed on cats with serious eye problems, such as incurable glaucoma, severe trauma, intraocular tumors, and treatment-resistant infections. This study, based on a narrative review of the literature of articles published between 2000 and 2023, analyzed surgical techniques, the impact of monocular vision loss, and the sensory adaptation of cats. The findings suggest that enucleation is generally well tolerated by cats, resulting in a satisfactory post-surgical recovery and improved quality of life, especially when performed correctly and with appropriate postoperative care. The switch to monocular vision occurs quickly, especially in cats with progressive vision loss. However, the initial adaptation phase can represent an obstacle, requiring a safe environment and constant support.